2014
DOI: 10.1016/s0140-6736(13)62302-8
|View full text |Cite
|
Sign up to set email alerts
|

Medical management with or without interventional therapy for unruptured brain arteriovenous malformations (ARUBA): a multicentre, non-blinded, randomised trial

Abstract: Summary Background The clinical benefit of preventive eradication of unruptured brain arteriovenous malformations remains uncertain. A Randomised trial of Unruptured Brain Arteriovenous malformations (ARUBA) aims to compare the risk of death and symptomatic stroke in patients with an unruptured brain arteriovenous malformation who are allocated to either medical management alone or medical management with interventional therapy. Methods Adult patients (≥18 years) with an unruptured brain arteriovenous malfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
664
7
31

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,043 publications
(714 citation statements)
references
References 31 publications
12
664
7
31
Order By: Relevance
“…At the conclusion of the trial, outcome data were available for only 223 subjects. 12 Further adding to the complexity of the problem is the heterogeneous nature of the disease. Specifically, there are five different groups of AVMs based on the Spetzler-Martin classification, each with a distinct natural history.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the conclusion of the trial, outcome data were available for only 223 subjects. 12 Further adding to the complexity of the problem is the heterogeneous nature of the disease. Specifically, there are five different groups of AVMs based on the Spetzler-Martin classification, each with a distinct natural history.…”
Section: Limitationsmentioning
confidence: 99%
“…The ICH risk for untreated AVMs is 2% to 6% per year. 2,[6][7][8] However, the annual hemorrhage risk may be as high as 34% if any additional risk factors are present. 9 History of hemorrhage, high blood pressure, intranidal aneurysm, venous stenosis, and deep venous drainage are the main factors that increase the likelihood of AVM rupture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual risk of hemorrhage depends on a number of factors, including location, drainage via the deep brain veins and the presence of an aneurysm in the feeder vessels [39]. Although a current study has demonstrated the superiority of conservative treatment of asymptomatic AVM [47], individual treatment remains a subject of discussion; therefore an examination in a neurovascular center is recommended (Category II).…”
Section: Arteriovenous Malformations (Avm)mentioning
confidence: 91%
“…12,13 In the face of recent reports suggesting that medical management may be superior to interventional therapy for unruptured AVMs, at least in the short term, such analyses become all the more critical. 14,15 Assembling a multidisciplinary team with expertise in the medical, surgical, endovascular, and radiation treatment of AVMs is critical for appropriately managing patients with this complex lesion.…”
Section: Introductionmentioning
confidence: 99%